Strategi Pengembangan Fasilitas Pariwisata Untuk Meningkatkan Jumlah Kunjungan Wisatawan Di Destinasi Wisata Pantai Labobo - B, Amin.; Nugroho, Rizky Arif; Dewanti, Ajeng Nugrahing; Astha, Dwinsani Pratiwi (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Labobo Beach is one of the tourist attractions that need to be developed because facilities in this tourist area are still inadequate; several facilities still need to be made available and are not managed well, especially in terms of basic facilities, complementary facilities and tourism supporting facilities, this is in line with the decline in the number of tourist visits to Labobo beach. The aim of the research can be formulated, namely, to prepare a strategy for developing tourism facilities that will be implemented to increase the number of tourist visits to Labobo Beach. The data collection method in this research was field observation to obtain data related to conditions of facilities, visitors and tourist locations, distributing questionnaires to visitors to find out the results of evaluations of facility conditions and to determine priority facilities to be developed, conducting interviews to obtain visitor data, availability of existing tourist facilities and conditions, and conducting literature surveys to produce variable indicators that used in research. Data is used in this research, namely evaluating the condition of facilities and analyzing priority facilities that must be developed. The results of assessing and analyzing these facilities are formulated into a SWOT strategy based on internal and external factors to obtain 21 facility development strategies Keywords : facilities, visitor strategy and development